Experimental Research on Stability and Transition in High-Speed Wakes. Part 3. Influence of Thickness of a Flat Plate and Length of its Stern on Stability of a Supersonic Wake - Lysenko, V.I. (Engineering Transactions, 1998)
The development of disturbances in a supersonic wake (free viscous layer and regular wake) behind a flat plate, both in linear and in nonlinear phases of development was investigated. The influence of several factors (Mach and Reynolds numbers, temperature factor, thickness of a plate, length of its stern) on the wake stability was studied.